EVALUASI TERHADAP ASPEK HIDROLOGI PADA KAWASAN RENCANA PENGEMBANGAN KOTA DI KOTA BALANGAN - Kurdi, Holdani; Novitasari, Novitasari (Jurnal Teknologi Berkelanjutan, 2020)
Urban growth is inseparable from the development of settlements, city facilities and infrastructure, and other supporting facilities. Urban growth also occurs in Balangan Regency, especially in Balangan City. The development of urban planning is inseparable from the hydrological factor of the area. This study aims to evaluate the existing water system in Balangan City on the hydrological aspects of the area, especially in the office area and city growth. The evaluation includes the existing water system in Balangan City, the existing conditions, and how to plan for the future. This study proves that the air system's condition, especially the drainage system in Balangan City, is not well integrated, which is indicated by the absence of a comprehensive network system, making it difficult to evaluate the existing air system. Fortunately, this can still be covered by the hilly topography of Balangan City and the land use that is still not compacted so that water infiltration into the ground can still be expected as a solution. The need for an integrated system by taking into account urban open spaces.